The impact of international achievement studies on national education policymaking - Wiseman, Alexander W. 1968- (International perspectives on education and society, 2010)
Since the IEAs first international studies on mathematics and science achievement in the late 1960s, the availability and use of international achievement studies around the world has exploded. The most widely adopted studies, PISA and TIMSS, are now administered regularly and include participating countries from every region around the world. These international studies, now include cross-national studies of multiple subject areas, teachers and teaching, and a developing focus on higher education. This information has been used to make decisions about resource distribution both within and across national educational systems, but some of the most productive uses of TIMSS and PISA data by policymakers have been to create agendas for innovation and equity in national educational systems. The chapters in this volume will (1) discuss the uses of international achievement study results as a tool for national progress as well as an obstacle, (2) provide recommendations for ways that international achievement data can be used in real-world policymaking situations, and (3) discuss what the future of international achievement studies holds.